2021
DOI: 10.3390/su13020747
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Evapotranspiration and Crop Coefficients of Bell Pepper Using a Removable Weighing Lysimeter: A Case Study in the Southeast of Spain

Abstract: Water use efficiency is essential in semiarid regions of Spain, and it can be achieved through a precise knowledge of the real crop water requirements (CWR). The Food and Agriculture Organization of the United Nations (FAO) offers standardized crop coefficients to establish the CWR. However, these coefficients can change due to different conditions, such as climatic variations and cultivation practices. In this work, the evapotranspiration (ETClys) and crop coefficients (KClys) of bell pepper were obtained wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…Hourly crop coefficients are needed to optimize the water application efficiency of high-frequency irrigation systems, even though they are rarely reported in the literature (Irmak et al 2013 ). Research over the past years has demonstrated that growth stage-specific K C values are also site-specific as they are sensitive to changes in air vapor density, air temperature, wind speed, and to a lesser degree to solar radiation (Annandale and Stockle 1994 ; Čerekovic et al 2010 ; Mulovhedzi et al 2020 ; Ávila-Dávila et al 2021 ). Particularly, the primary limitation in semi-arid regions for estimating greenhouse K C values is related to the energy and mass fluxes of the greenhouse atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Hourly crop coefficients are needed to optimize the water application efficiency of high-frequency irrigation systems, even though they are rarely reported in the literature (Irmak et al 2013 ). Research over the past years has demonstrated that growth stage-specific K C values are also site-specific as they are sensitive to changes in air vapor density, air temperature, wind speed, and to a lesser degree to solar radiation (Annandale and Stockle 1994 ; Čerekovic et al 2010 ; Mulovhedzi et al 2020 ; Ávila-Dávila et al 2021 ). Particularly, the primary limitation in semi-arid regions for estimating greenhouse K C values is related to the energy and mass fluxes of the greenhouse atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…En este sentido, se enumeran las principales actuaciones que se han realizado: Se han analizado los cultivos objetivo de un lisímetro de pesada para establecer las dimensiones óptimas para hacerlo estándar (1); se han desarrollado ensayos en campo a fin de obtener un equipo de lisimetría robusto y fiable, cuya información sea útil para el agricultor, dando lugar a bastantes algoritmos (2,6,7); se ha trabajado con sensores de humedad de menor coste (8,9); se ha trabajado para incorporar información agroclimática pública para el empleo en las decisiones del manejo de riego (10).…”
Section: Monitorización De Variables Agroclimáticasunclassified